Multi-layer microporous polyolefin membrane, its manufacturing method, and laminated multi-layer microporous membrane
By dispersing regions with constant polypropylene concentration in micron size within a multilayer polyolefin microporous membrane, the challenges of maintaining mechanical strength, meltdown properties, and air permeability resistance in thin membranes are addressed, resulting in a membrane suitable for high-capacity battery separators.
Patent Information
- Application Number
- JP2021569092
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-29
- Filing Date
- 2021-10-28
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-10-28
AI Technical Summary
Existing polyolefin multilayer microporous membranes struggle to maintain both mechanical strength and meltdown properties when thinned to 6 μm or less, while also ensuring adequate air permeability resistance, which is crucial for high-capacity lithium-ion batteries.
The membrane is designed with a specific structure where regions with a constant polypropylene concentration are dispersed in micron size, allowing even thin membranes to achieve sufficient mechanical strength, air resistance, and meltdown properties. This is achieved through a multilayer structure with a Raman strength ratio of polypropylene to polyethylene between 0.018 and 0.040, and a network structure covering 68% or more of the surface area.
The resulting polyolefin multilayer microporous membrane exhibits excellent mechanical strength, meltdown properties, and air permeability resistance even when thinned, making it suitable for high-capacity battery separators.
Smart Images

Figure 0007647585000003 
Figure 0007647585000004 
Figure 0007647585000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a multi-layer, microporous polyolefin membrane and a method for producing the same, and more particularly to a multi-layer, microporous polyolefin membrane that has high mechanical strength and meltdown properties even when made thin and can be suitably used for battery separators and the like, and a method for producing the same. [Background technology]
[0002] Microporous membranes are used in various fields, such as filtration membranes, battery separators, and separators for electrolytic capacitors. In particular, polyolefin microporous membranes that have excellent chemical resistance, mechanical strength, and shutdown properties are used as battery separators. Furthermore, lithium ion battery separators are required to have higher meltdown properties and mechanical strength from the viewpoint of safety.
[0003] Patent Document 1 describes that a multi-layer, microporous polyolefin membrane consisting of a microporous layer made of polyethylene and a microporous layer containing polypropylene has excellent foreign matter resistance at high temperatures.
[0004] Patent Document 2 discloses a monolayer film made of polypropylene and polyethylene, and the concentration and distribution of polypropylene that are effective for oxidation resistance.
[0005] Patent Document 3 discloses a microporous polyolefin film having excellent heat resistance, which is obtained by blending homopolypropylene with copolymer polypropylene to increase the compatibility between polyethylene and polypropylene. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2020 / 149294 [Patent Document 2] International Publication No. 2013 / 099607 [Patent Document 3] JP 2010-235654 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, Patent Documents 1 to 3 are unable to achieve both the meltdown properties and mechanical strength in a thin film of 6 μm or less, which will be required in the future. In recent years, in order to further increase the capacity of lithium-ion batteries, there has been a demand for a thinner microporous film, and there has also been an increasing demand for mechanical strength and meltdown properties that maintain the safety of batteries at high temperatures. By making the film thin, the basis weight of the resin that constitutes the microporous film is reduced, which makes it difficult to maintain the meltdown properties and mechanical strength. In addition, since the air resistance increases when the porosity is reduced to maintain strength, a thin film of 6 μm or less has an insufficient balance between heat resistance, strength, and air resistance required for a battery separator.
[0008] Therefore, an object of the present invention is to provide a multi-layer, microporous polyolefin membrane which has excellent mechanical strength and meltdown properties and good air resistance even when made thin. [Means for solving the problem]
[0009] The present inventors discovered that by dispersing and arranging regions having a certain polypropylene concentration in a micron-sized area, even a thin microporous membrane made of a small amount of polypropylene can have sufficient mechanical strength and air resistance as a battery separator and can also exhibit good meltdown properties, and thus arrived at the present invention.
[0010] That is, the present invention is a multi-layer, microporous polyolefin membrane comprising a first layer containing polypropylene and polyethylene and a second layer made of polyethylene, and satisfying the following requirements (I) and (II). (I) The polyolefin multi-layer, microporous membrane has regions in which the Raman intensity ratio of polypropylene to polyethylene is 0.018 or more and 0.040 or less, as determined by micro-Raman spectroscopy, and a network structure in which the regions are interconnected occupies 68% or more of the surface area of the polyolefin multi-layer, microporous membrane, and the coefficient of variation of the Raman intensity ratio of PP / PE is 8% or more and 30% or less. (II) The puncture strength per unit area of the multi-layer, microporous polyolefin membrane (N m 2 / g) divided by the maximum pore size (μm) is 13 or more and 30 or less.
[0011] The present invention also relates to a laminated multi-layer, microporous membrane comprising a porous layer laminated on at least one surface of the polyolefin multi-layer, microporous membrane of the present invention.
[0012] The present invention also relates to a method for producing the multi-layer, microporous polyolefin membrane of the present invention, which comprises the following steps (1) to (6): (1) A step of melt-kneading a first polyolefin resin including polypropylene and polyethylene with a membrane-forming solvent to prepare a first polyolefin solution; (2) melt-kneading a second polyolefin resin containing polyethylene with a membrane-forming solvent to prepare a second polyolefin solution; (3) co-extruding the first and second polyolefin solutions and cooling to form a gel-like multilayer sheet; (4) a first stretching step of stretching the gel-like multilayer sheet at 107°C or more and 112°C or less; (5) removing the membrane-forming solvent from the stretched gel-like multilayer sheet and drying it; (6) A second stretching step of stretching the dried multilayer sheet at 95° C. to 130° C. at 1.55 times or more in TD. Effect of the Invention
[0013] The multi-layer, microporous polyolefin membrane of the present invention has excellent mechanical strength and meltdown properties even when made thin, and has good air resistance. In particular, the multi-layer, microporous polyolefin membrane of the present invention is suitable for use as a separator for high-capacity batteries. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a two-dimensional distribution diagram of the Raman intensity ratio of PP / PE in Example 1. [Diagram 2] FIG. 2 is a histogram of the Raman intensity ratio of PP / PE in Example 1. [Diagram 3] FIG. 3 is a two-dimensional distribution diagram of the Raman intensity ratio of PP / PE in Example 2. [Figure 4] FIG. 4 is a two-dimensional distribution diagram of the Raman intensity ratio of PP / PE in Comparative Example 1. [Diagram 5] FIG. 5 is a two-dimensional distribution diagram of the Raman intensity ratio of PP / PE in Comparative Example 2. [Explanation of symbols]
[0015] a Region where the Raman intensity ratio of PP / PE is 0.018 or more and 0.040 or less. b Region where the Raman intensity ratio of PP / PE is greater than 0.040 c Region where the Raman intensity ratio of PP / PE is less than 0.018 1~11: Coordinate number DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The multi-layer, microporous polyolefin membrane of the present invention comprises a first layer comprising polypropylene and polyethylene, and a second layer made of polyethylene.
[0017] (polypropylene) The polypropylene contained in the first layer may be a propylene homopolymer, a copolymer of propylene with other α-olefins and / or diolefins (propylene copolymer), or a mixture thereof. Among them, it is preferable to use a propylene homopolymer from the viewpoints of mechanical strength, miniaturization of through-hole diameter, high melting point, etc.
[0018] The weight average molecular weight Mw of the polypropylene contained in the first layer is 1×10 6 More than 3×10 6 It is preferable that it is less than 1000 .mu.m.
[0019] The polypropylene content in the first layer is preferably 8% by mass or more. By making the polypropylene content 8% by mass or more, more preferably 10% by mass or more, the heat resistance of the multi-layer microporous membrane can be effectively improved. In addition, the polypropylene content in the first layer is preferably 50% by mass or less. By making the polypropylene content 50% by mass or less, more preferably 35% by mass or less, the maximum pore size of the microporous membrane can be prevented from becoming small, and the air resistance can be prevented from increasing. By making the polypropylene content within the above range, the polypropylene can be easily dispersed and arranged in the polyethylene in the melt kneading process, and when the microporous membrane is formed under the process conditions described below, the variation coefficient of the Raman intensity ratio of PP / PE can be adjusted within the range described below.
[0020] The polypropylene content in the first layer can be determined by measuring a cross section of the multi-layer, microporous polyolefin membrane by AFM-IR.
[0021] The polypropylene content in the multi-layer, microporous polyolefin membrane is preferably 3.0% by mass or more in order to increase the meltdown temperature, and the polypropylene content in the multi-layer, microporous polyolefin membrane is preferably less than 8.0% by mass in order to improve the mechanical strength and reduce the air resistance.
[0022] By setting the polypropylene content in the multi-layer, microporous membrane within the above preferred range and carrying out membrane production under the process conditions described below, it is easy to adjust the proportion of the surface area of the polyolefin multi-layer, microporous membrane that has regions with a PP / PE Raman intensity ratio of 0.018 or more and 0.040 or less and has a network structure in which such regions are interconnected, to within the range described below.
[0023] (polyethylene) As the polyethylene in the multi-layer, microporous polyolefin membrane of the present invention, not only ethylene homopolymers but also ethylene-α-olefin copolymers containing small amounts of other α-olefins can be used.
[0024] The polyethylene in the multi-layer, microporous polyolefin membrane of the present invention has a density of 0.920 g / m 3 More than 0.970g / m 3 It is preferable that the polyolefin resin contains a high-density polyethylene having a molecular weight of 100 or less and a molecular weight of 110 or less, and a high-density polyethylene having a molecular weight of 100 or less is contained. By containing a high-density polyethylene, the shutdown temperature can be lowered, and the strength and maximum pore size of the multi-layer, microporous membrane can be effectively set within the range of the present invention.
[0025] The weight average molecular weight Mw of high density polyethylene is 1×10 4 More than 1×10 6 It is preferable that it is less than 1000 .mu.m.
[0026] The multi-layer, microporous polyolefin membrane of the present invention has a weight average molecular weight Mw of 1×10 6 It is preferable that the polyolefin multi-layer, microporous membrane contains the above ultra-high molecular weight polyethylene. By containing the ultra-high molecular weight polyethylene, it is possible to effectively achieve high strength, small maximum pore size, and pin puncture strength as described below for the multi-layer, microporous polyolefin membrane.
[0027] (Other resin components) The multi-layer, microporous polyolefin membrane of the present invention may contain other resin components, preferably heat-resistant resins.
[0028] (Layer structure) The multi-layer, microporous polyolefin membrane of the present invention can have three or more layers by providing layers other than the first and second layers.
[0029] The multi-layer, microporous polyolefin membrane of the present invention preferably has a three-layer structure in which the layers are laminated in the order of first layer / second layer / first layer or second layer / first layer / second layer.
[0030] (Network Structure) The polyolefin multi-layer microporous membrane of the present invention has a region in which the Raman intensity ratio of polypropylene to polyethylene (PP / PE) obtained by microscopic Raman spectroscopy is 0.018 or more and 0.040 or less. By making the Raman intensity ratio of PP / PE 0.018 or more, preferably 0.019 or more, it is possible to effectively prevent melting of the resin at high temperatures and meltdown due to opening of holes. In addition, by making the Raman intensity ratio of PP / PE 0.040 or less, preferably 0.038 or less, it is possible to effectively prevent a decrease in mechanical strength and an increase in air resistance.
[0031] The PP / PE Raman intensity ratio was measured by irradiating the surface of a polyolefin microporous film with a laser having a wavelength of 532 nm and a spot diameter of 4 μm using a microscopic laser Raman spectrophotometer (RS-5100, manufactured by JASCO Corporation) and measuring the Raman shift of 810 cm -1 Peak intensities I(810) and 1130cm -1 The Raman intensity ratio of PP / PE is calculated from the peak intensity I(1130). I(810) indicates the presence of polypropylene and I(1130) indicates the presence of polyethylene. The Raman intensity ratio of PP / PE is calculated using the following formula: Raman intensity ratio of PP / PE = I(810) / I(1130) ... (equation).
[0032] The above-mentioned "area" is divided into 121 measurement points, 11 points at 7 μm intervals in each direction of the microporous membrane, and the measurement range of each point is a region of 7 μm × 7 μm in length and width, with the laser spot at the center.
[0033] Hereinafter, the region in the above fraction that satisfies the above PP / PE Raman intensity ratio is referred to as the "specific region."
[0034] The polyolefin multilayer microporous membrane of the present invention has a network structure in which the specific regions are interconnected. Here, "interconnected" means that when focusing on one specific region in the above-mentioned fractionation, at least one of the eight regions surrounding it is also a specific region. In addition, the "network structure" means a structure in which 16 or more specific regions are interconnected together.
[0035] In the polyolefin multi-layer, microporous membrane of the present invention, the network structure accounts for 68% or more of the entire membrane. When the network structure accounts for 68% or more, preferably 74% or more, more preferably 80% or more of the entire membrane, a microporous membrane having good meltdown properties and both mechanical strength and air resistance can be obtained.
[0036] Considering that the network structure accounts for 68% or more of the whole in light of the above-mentioned "region" fractionation, 83 or more of the total 121 regions contribute to the formation of the network structure.
[0037] In Fig. 1, as a measurement result of a polyolefin multilayer microporous membrane (Example 1) having a relatively high PP content, 11 regions at 7 μm intervals in the machine direction (MD) and the transverse direction (TD) are shown according to the Raman intensity ratio of PP / PE. The symbol a represents a region where the Raman intensity ratio of PP / PE is 0.018 or more and 0.040 or less, and the symbol b represents a region where the Raman intensity ratio of PP / PE is more than 0.040. By surrounding and isolating the region with a high polypropylene ratio with the network structure, the influence is localized, and it becomes easy to obtain sufficient mechanical strength and low air resistance as a battery separator.
[0038] The distribution of Raman intensities for the PP / PE example in Figure 1 is shown in the histogram in Figure 2.
[0039] In Fig. 3, as a measurement result of a polyolefin multilayer microporous membrane (Example 2) with a relatively low PP content, 11 regions are shown at 7 μm intervals in the machine direction (MD) and the transverse direction (TD) according to the Raman intensity ratio of PP / PE. The symbol a represents a region where the Raman intensity ratio of PP / PE is 0.018 or more and 0.040 or less, and the symbol c represents a region where the Raman intensity ratio of PP / PE is less than 0.018. By surrounding and isolating the region with a low polypropylene ratio with the network structure, the influence is localized, and even at a high temperature where polyethylene melts, the surrounding region with a high polypropylene content holds the melted part, preventing hole opening and meltdown, and maintaining the shutdown state.
[0040] As described above, the multi-layer, microporous polyolefin membrane of the present invention has the above-mentioned network structure, and therefore can have good meltdown properties, mechanical strength, and low air resistance even when it is thin.
[0041] The PP / PE Raman intensity ratio and its proportion can be adjusted by appropriately adjusting the polypropylene content in the multi-layer, microporous membrane and the membrane-forming conditions described below.
[0042] The polyolefin multi-layer microporous membrane of the present invention has a coefficient of variation of the Raman intensity ratio of PP / PE of 8% or more and 30% or less. By making the coefficient of variation of the Raman intensity ratio of PP / PE 30% or less, preferably 25% or less, it is possible to suppress non-uniformity of polypropylene distribution and suppress variations in heat resistance and air resistance. In addition, by making the coefficient of variation of the Raman intensity ratio of PP / PE 8% or more, preferably 10% or more, it is possible to suppress excessive uniform dispersion of polypropylene, suppress the amount of polypropylene required to obtain sufficient heat resistance, and suppress deterioration of mechanical strength.
[0043] The coefficient of variation of the PP / PE Raman intensity ratio is calculated by calculating the standard deviation from the 121 points of the PP / PE Raman intensity ratios and dividing it by the average value of the Raman intensity ratios.
[0044] The coefficient of variation of the Raman intensity ratio of PP / PE can be adjusted by appropriately adjusting the polypropylene content in the multi-layer, microporous membrane and the membrane-forming conditions described below.
[0045] The polyolefin multi-layer, microporous membrane of the present invention has a half-value width of the Raman band of polypropylene measured by micro-Raman spectroscopy of 7.20 cm. -1 The crystallinity of polypropylene is measured by Raman spectroscopy at a wavelength of 400 cm or less. -1 The half-width of the Raman band observed around the center of the nucleus is 7.20 cm. -1 Less than or equal to 7.15cm, more preferably -1 By ensuring that the thickness is equal to or less than this, the melting point of the polypropylene contained in the first layer is increased, making it possible to obtain a microporous membrane that has high heat resistance even though it is a thin film.
[0046] (Mechanical strength and pore structure) The multi-layer, microporous polyolefin membrane of the present invention has a puncture strength per unit area (N m 2 / g) divided by the maximum pore size (μm) is 13 to 30. In order to achieve both the mechanical strength and air resistance required for a battery and to achieve the properties required for a battery separator, the puncture strength (N·m 2 The value obtained by dividing the pore size (μm) by the maximum pore size (μm) must be 13 or more and 30 or less, and more preferably 15 or more and 25 or less.
[0047] The puncture strength per unit area is preferably 0.60N·m 2 / g or more. The puncture strength per unit area is 0.60 N m 2 / g or more, preferably 0.68 N m 2 / g or more, the resistance to foreign matter during battery assembly is good even for thin separators, resulting in excellent battery yields. In addition, the puncture strength per unit area is 1.20 N·m 2 / g or less. The puncture strength per unit area is 1.20 N m 2 / g or less, preferably 1.10 N m 2 / g or less, it is possible to suppress thermal shrinkage at high temperatures and suppress deterioration of meltdown properties.
[0048] The maximum pore size is preferably 0.020 μm or more and 0.060 μm or less. By making the maximum pore size 0.020 μm or less, more preferably 0.025 μm or more, the increase in air permeability resistance can be suppressed, and when used as a battery separator, the decrease in output characteristics of the battery due to the increase in ion resistance can be suppressed. In addition, by making the maximum pore size 0.060 μm or less, more preferably 0.055 μm or less, the decrease in withstand voltage can be suppressed, and the decrease in battery yield can be suppressed.
[0049] The mechanical strength and maximum pore size can be controlled by the resin components and process described below.
[0050] The polyolefin multi-layer, microporous membrane of the present invention preferably has a porosity of 20% or more and 50% or less. With a porosity of 20% or more, the air resistance can be suppressed, and even when used as a battery separator, the ionic resistance can be suppressed. Furthermore, with a porosity of 50% or less, the mechanical strength can be effectively maintained.
[0051] (Film thickness) The multi-layer, microporous polyolefin membrane of the present invention preferably has a thickness of 6 μm or less, which allows the battery to have a higher capacity and output.
[0052] (Laminated multi-layer microporous membrane) The laminated multi-layer, microporous membrane of the present invention is obtained by laminating a porous layer on at least one surface of the polyolefin multi-layer, microporous membrane of the present invention. By laminating a porous layer, a battery separator having excellent heat resistance and adhesiveness to electrodes can be obtained.
[0053] An example of the porous layer may include a layer containing inorganic particles and a resin binder.
[0054] (Application) The polyolefin multi-layer, microporous membrane of the present invention and the laminated multi-layer, microporous membrane of the present invention can be suitably used as a battery separator.
[0055] (Method for producing a multi-layer, microporous polyolefin membrane) The method for producing a multi-layer, microporous polyolefin membrane of the present invention includes the following steps (1) to (6). (1) A step of melt-kneading a first polyolefin resin composition containing polypropylene and polyethylene with a membrane-forming solvent to prepare a first polyolefin solution; (2) melt-kneading a second polyolefin resin composition containing polyethylene with a membrane-forming solvent to prepare a second polyolefin solution; (3) co-extruding the first and second polyolefin solutions and cooling to form a gel-like multilayer sheet; (4) a first stretching step of stretching the gel-like multilayer sheet at 107°C or more and 112°C or less; (5) removing the membrane-forming solvent from the stretched gel-like multilayer sheet and drying it; (6) A second stretching step of stretching the dried multilayer sheet in the width direction at 1.55 times or more at 95° C. to 130° C. In steps (2), (4), and (6), by controlling the resin concentration, stretching temperature, and stretching ratio of each layer within the ranges described below, it is possible to form a thin membrane without rupturing, thereby achieving high mechanical strength and meltdown resistance and providing a multi-layer, microporous membrane with good air resistance.
[0056] Each step will be described below.
[0057] (1) and (2) Preparation of the first and second polyolefin solutions A suitable membrane-forming solvent is added to the polyolefin resin composed of polypropylene and polyethylene contained in the first layer and the polyolefin resin composed of polyethylene contained in the second layer, and then melt-kneaded to prepare a first polyolefin solution and a second polyolefin solution, respectively. As a melt-kneading method, for example, a method using a twin-screw extruder described in the specifications of Japanese Patent No. 2132327 and Japanese Patent No. 3347835 can be used.
[0058] From the viewpoint of forming a polypropylene network structure, the ratio of the plasticizer added to the first polyolefin resin is preferably 70% by mass or more and 90% by mass or less. By setting the ratio of the plasticizer added within the above range, the polypropylene in the plasticizer is dispersed and arranged in the polyethylene, and when stretched in a later process, it becomes possible to form a structure in which the polypropylene is connected in a network shape at a certain concentration.
[0059] (3) Gel-like sheet formation process The first and second polyolefin solutions are fed from the extruders to a die, where the two solutions are combined in layers and extruded into a sheet. The resulting laminated extrudate is cooled to form a gel-like multi-layer sheet. The gel-like sheet can be formed, for example, by the methods disclosed in Japanese Patent No. 2132327 and Japanese Patent No. 3347835.
[0060] (4) First stretching step Next, the obtained gel-like multilayer sheet is biaxially stretched. Any of simultaneous biaxial stretching, sequential stretching, and multi-stage stretching (for example, a combination of simultaneous biaxial stretching and sequential stretching) may be used. Since the gel-like multilayer sheet contains a membrane-forming solvent, it can be stretched uniformly. After heating, the gel-like multilayer sheet may be stretched at a predetermined ratio, and from the viewpoint of strength, the areal stretching ratio is preferably 25 times or more.
[0061] In the first stretching step, the gel-like multilayer sheet is stretched at a temperature ranging from 107° C. to 112° C. to adjust the film properties. If the stretching temperature is less than 107° C., the stretching stress applied to the gel-like multilayer sheet becomes too large, which may lead to film breakage and reduce productivity. If the stretching temperature is more than 112° C., the stretching stress applied to the gel-like multilayer sheet becomes too small, which makes it difficult to obtain the mechanical strength required for a thin film, such as pin puncture strength.
[0062] In addition, such stretching conditions improve the crystallinity of the polypropylene contained in the first layer, increasing the melting point of the polypropylene contained in the first layer and making it possible to obtain a microporous membrane with high heat resistance even though it is a thin film.
[0063] (5) Removal of membrane-forming solvent and drying The membrane-forming solvent is removed (washed) using a washing solvent. Since the first and second polyolefin phases are phase-separated from the membrane-forming solvent phase, when the membrane-forming solvent is removed, a porous membrane is obtained that is made of fibrils that form a fine three-dimensional network structure and has three-dimensionally irregularly interconnected pores (voids).
[0064] The multi-layer, microporous membrane from which the membrane-forming solvent has been removed is dried by heat drying or air drying.
[0065] (6) Second stretching step The dried multi-layer, microporous membrane is preferably stretched at least in the width direction.
[0066] The multi-layer, microporous membrane can be stretched while being heated by a tenter method or the like in the same manner as in (4) above. The stretching may be uniaxial or biaxial. In the case of biaxial stretching, either simultaneous biaxial stretching or sequential stretching may be used.
[0067] The stretching temperature in this step is preferably from 95° C. to 130° C. When the film is re-stretched within the above range, the film is stretched while being sufficiently kept warm, so that a multi-layer, microporous membrane that is less likely to break during stretching and has excellent mechanical strength can be obtained.
[0068] The stretching ratio in the uniaxial direction of the multi-layer, microporous membrane in this step is preferably 1.55 to 2.4 times. In the case of biaxial stretching, the areal stretching ratio is preferably 1.4 to 4.0 times, and is preferably 1.2 to 2.0 times in MD and TD, respectively, and the stretching ratios in MD and TD may be the same or different from each other.
[0069] Moreover, by setting such stretching conditions, the puncture strength per unit area weight becomes sufficiently high for a battery separator, and the crystallinity of the polypropylene is further improved.
[0070] The dried multi-layer, microporous membrane can be subjected to a heat treatment, which is a heat treatment in which the membrane is heated while maintaining its dimensions constant, or a heat treatment in which the membrane is contracted in the MD or TD during heating.
[0071] In steps (2), (4), and (6), by carrying out the resin concentration, stretching temperature, and stretching ratio of each layer within the above-mentioned ranges, cleavage occurs between the polyethylene lamellae, the polyethylene phase becomes fine, and a large number of fibrils are formed. The fibrils form a three-dimensionally irregularly connected network structure. The polypropylene dispersed in the gel-like sheet is also stretched and finely divided together with the polyethylene, and a network structure is formed over the entire surface of the multi-layer microporous membrane, and a network structure can be obtained in which the Raman intensity ratio of PP / PE determined by micro-Raman spectroscopy and its coefficient of variation are as set forth in the claims.
[0072] By using the above-mentioned film-forming conditions, it is possible to obtain a thin, highly heat-resistant, multi-layer, microporous film having the mechanical strength required for a battery separator, small pore size, and excellent output characteristics. EXAMPLES
[0073] The present invention will be described in more detail with reference to examples, but the embodiments of the present invention are not limited to only these examples.
[0074] The evaluation and analysis methods used in the examples are as follows.
[0075] [Evaluation method, analysis method] (1) Film thickness (μm) The thickness of a sample (95 mm × 95 mm) cut out from the polyolefin microporous membrane obtained in the examples was measured at five locations, including the center, ±30 mm in MD from the center, and ±30 mm in TD, to obtain an average thickness. A contact thickness meter ("Litematic" manufactured by Mitutoyo Corporation) equipped with a carbide spherical probe of φ10.5 (part number 120060) and a measuring force of about 0.15 N was used for the measurement.
[0076] (2) Porosity (%) The volume (cm) of the sample (95 mm x 95 mm) cut out from the polyolefin microporous membrane obtained in the examples 3 The porosity (%) was calculated from the results using the following formula: The density of the resin constituting the microporous membrane was 0.99 g / cm 3 was used. Porosity=(1-sample mass / (0.99×sample volume))×100...(formula).
[0077] (3) Air permeability resistance (sec / 100cm 3 ) The polyolefin microporous membranes obtained in the examples were measured for air resistance (sec / 100 cm) using an air resistance meter (EGO-1T, manufactured by Asahi Seiko Co., Ltd.) in accordance with JIS P8117:2009. 3 ) was measured.
[0078] (4) Maximum pore diameter (μm) Using a perm porometer (CFP-1500A, manufactured by PMI), pressure was applied in the order of dry-up and wet-up to measure the maximum pore size. For wet-up, pressure was applied to a microporous membrane sufficiently immersed in perfluoropolyether (surface tension 15.9 dyne / cm, Galwick (trade name) manufactured by PMI) as a liquid with a known surface tension, and the pore size calculated from the pressure at which air began to penetrate was taken as the maximum pore size.
[0079] (5)Piercing strength (N) The puncture strength was determined as the maximum load when the center of a sample (95 mm x 95 mm) cut out from the polyolefin microporous membrane obtained in the Examples was pierced with a 1 mm diameter needle with a spherical tip (radius of curvature R: 0.5 mm) at a speed of 2 mm / sec.
[0080] (6) Shutdown temperature, meltdown temperature The polyolefin microporous membrane obtained in the examples was exposed to an atmosphere of 30°C and heated at a rate of 5°C / min, during which the air resistance of the membrane was measured. 5 sec / 100cm 3 The temperature at which the air resistance exceeds 1×10 was defined as the shutdown temperature of the microporous membrane. 5 sec / 100cm 3 The temperature at which the meltdown temperature was less than this was determined and recorded as the meltdown temperature (° C.) The air resistance of the microporous membrane was measured in accordance with JIS P8117:2009 using an air resistance meter (EGO-1T, manufactured by Asahi Seiko Co., Ltd.).
[0081] (7) Weight average molecular weight (Mw) The Mw of UHMWPE and HDPE was determined by gel permeation chromatography (GPC) under the following conditions. Measurement equipment: Waters Corporation GPC-150C Column: Showa Denko ShodexUT806M Column temperature: 135℃ Solvent (mobile phase): o-dichlorobenzene Solvent flow rate: 1.0ml / min Sample concentration: 0.1wt% (dissolution conditions: 135℃ / 1h) Injection volume: 500μl Detector: Waters Corporation differential refractometer (RI detector) Calibration curve: A calibration curve was prepared using a specific conversion constant from a calibration curve obtained using a monodisperse polystyrene standard sample.
[0082] (8) Heat of fusion, melting point Heat of fusion ΔH m was measured according to the following procedure in accordance with JIS K7122. That is, the sample was placed in the sample holder of a differential scanning calorimeter (DSC-System 7 model, manufactured by PerkinElmer, Inc.), heat-treated at 190°C for 10 minutes in a nitrogen atmosphere, cooled to 40°C at 10°C / min, held at 40°C for 2 minutes, and heated to 190°C at a rate of 10°C / min. A straight line passing through the points at 85°C and 175°C on the DSC curve (melting curve) obtained during the heating process was drawn as a baseline, and the amount of heat (unit: J) was calculated from the area enclosed by the baseline and the DSC curve, and this was divided by the weight of the sample (unit: g) to obtain the heat of fusion ΔH m (unit: J / g) was calculated. Similarly, the heat of fusion ΔH m The temperature at the minimum in the endothermic melting curve was measured as the melting point.
[0083] (9) Polypropylene distribution (PP / PE Raman intensity ratio), network structure fraction, and coefficient of variation of Raman intensity ratio A 95 mm x 95 mm sample piece cut out from a polyolefin microporous membrane was used.
[0084] Using a microscopic laser Raman spectrophotometer (RS-5100, manufactured by JASCO Corporation), a laser with a wavelength of 532 nm and a spot diameter of 4 μm was irradiated onto the surface of the sample piece.
[0085] A total of 121 measurement points were measured, 11 points at 7 μm intervals in both directions from the center of the sample piece. The measurement range for each point was set to an area of 7 μm × 7 μm in both directions so that the laser spot was at the center. The measurement range was 77 μm × 77 μm in both directions. The Raman shift of polypropylene was 810 cm -1 , the Raman shift of polyethylene is 1130cm -1 And 810cm -1 Peak intensity I(810) and 1130cm -1From the peak intensity I (1130), the peak intensity ratio of polypropylene to polyethylene (PP / PE Raman intensity ratio) at each measurement point was calculated using the following formula. Raman intensity ratio of PP / PE = I(810) / I(1130) Regions where the PP / PE Raman intensity ratio was 0.018 or more and 0.040 or less (specific regions), regions where it was less than 0.018, and regions where it was more than 0.040 were mapped to correspond to positions in a measurement range of 77 μm × 77 μm. Then, when focusing on one specific region, a relationship in which at least one of the eight regions surrounding it was also a specific region was defined as a "network structure," and the number of specific regions forming this network structure was counted, and the network structure fraction (%) was calculated as the fraction relative to the total number of regions, which was 121.
[0086] In addition, the coefficient of variation (standard deviation / average value) of the Raman intensity ratio of PP / PE of the polyolefin microporous membrane was calculated from the average value and standard deviation of the Raman intensity ratio of PP / PE at 121 points.
[0087] (10) Half-width of the Raman band attributed to polypropylene (PP half-width) A 95 mm x 95 mm sample piece cut out from a polyolefin microporous membrane was used.
[0088] Using a microscopic laser Raman spectrophotometer (ivVia, manufactured by RENISHAW), the surface of the sample piece was irradiated with a laser having a wavelength of 532 nm and a spot diameter of 2 μm, and the measurement was performed.
[0089] The crystallinity of polypropylene is 400 cm -1 The half-width of the Raman band observed near the center of the sample was measured at three points, namely, the center and MD of ±30 mm from the center, and the average half-width of the Raman band at the three points was calculated to obtain the PP half-width.
[0090] (11) Mechanical strength Calculate the puncture strength per unit area from the puncture strength measured in (5) above, and obtain 0.6 N m 2 / g or more is good, 0.6N·m 2 / g was rated as poor.
[0091] (12) Output characteristics When used as a battery separator, it improves the output characteristics of the battery by reducing the ionic resistance. The air resistance of the microporous membrane is 150sec / 100cm 3 Less than 150sec / 100cm is good 3 The above was evaluated as poor.
[0092] (13) High temperature shape retention properties In order to maintain an insulating state and withstand inertial heat generation even after the battery abnormally heats up and the shutdown function is activated, it is preferable for the membrane to have high heat resistance, specifically, it is preferable for the microporous membrane to have a high meltdown temperature. Therefore, the meltdown temperature, which is the high-temperature shape retention property of the microporous membrane, was evaluated as good at 165°C or higher and poor at less than 165°C.
[0093] [Example 1] (Preparation of First Polyolefin Solution) Mw is 2.0×10 6 20 parts by mass of polypropylene (PP, melting point 162°C) and Mw of 5.6 x 10 5 High density polyethylene (HDPE, density 0.955g / cm 3 A resin mixture was prepared by blending 0.2 parts by mass of an antioxidant tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane with 100 parts by mass of a first polyolefin resin consisting of 80 parts by mass of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane (melting point 135°C). 25 parts by mass of the obtained resin mixture was put into a twin-screw extruder (1), and 75 parts by mass of liquid paraffin (35 cSt (40°C)) was fed as a membrane-forming solvent from the side feeder of the twin-screw extruder (1), and melt-kneaded to prepare a first polyolefin solution.
[0094] (Preparation of Second Polyolefin Solution) Mw is 2.0×10 6 40 parts by mass of ultra-high molecular weight polyethylene (UHMwPE) and Mw of 5.6 × 10 5 HDPE (density 0.955g / cm 3A resin mixture was prepared by blending 0.2 parts by mass of the antioxidant tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane with 100 parts by mass of a second polyolefin resin consisting of 60 parts by mass of tetrakis[methylene-3-(3,5-ditertiarybutyl-4-hydroxyphenyl)-propionate]methane. 28.5 parts by mass of the obtained resin mixture was put into a twin-screw extruder (2) separate from the twin-screw extruder (1), and 71.5 parts by mass of liquid paraffin (35 cSt (40°C)) was fed as a membrane-forming solvent from the side feeder of the twin-screw extruder (2) and melt-kneaded to prepare a second polyolefin solution.
[0095] (Extrusion) The first and second polyolefin solutions were fed from each twin-screw extruder to a three-layer T-die and extruded so that the layer ratio of the first polyolefin solution / the second polyolefin solution / the first polyolefin solution was 12.5 / 75 / 12.5. The extrudate was cooled while being taken up by a cooling roll to form a gel-like three-layer sheet.
[0096] (First extension) The gel-like three-layer sheet was simultaneously biaxially stretched (first stretching) at 110° C. by 5 times in both MD and TD using a tenter stretching machine.
[0097] (Removal of membrane-forming solvent, drying) The gel-like three-layer sheet that had been subjected to the first stretching was immersed in a methylene chloride bath in a washing tank to remove the liquid paraffin, and then air-dried at room temperature to obtain a dry film.
[0098] (Second extension) The dried membrane was stretched 1.59 times in TD at 128° C. using a batch-type stretching machine (second stretching).
[0099] (Heat treatment) The three-layer sheet that had been subjected to the second stretching was then relaxed at 128° C. for 0.85 times the TD.
[0100] The blending ratio of each component of the produced multi-layer, microporous polyolefin membrane, production conditions, evaluation results, etc. are shown in Table 1. A two-dimensional distribution diagram showing the Raman intensity ratio of PP / PE in Example 1 is shown in Figure 1. A histogram of the Raman intensity ratio of PP / PE in Example 1 is shown in Figure 2.
[0101] [Examples 2 and 3] In Examples 2 and 3, a multi-layer, microporous polyolefin membrane was produced in the same manner as in Example 1 except for the conditions shown in Table 1.
[0102] A two-dimensional distribution diagram of the Raman intensity ratio of PP / PE in Example 2 is shown in FIG.
[0103] [Example 4] The first and second polyolefin solutions were prepared using HDPE with Mw of 8.0×10 4 As UHMwPE, Mw is 1.5×10 6 Other than the conditions shown in Table 1, a multi-layer, microporous polyolefin membrane was produced in the same manner as in Example 1.
[0104] [Example 5] A multi-layer, microporous polyolefin membrane was produced in the same manner as in Example 4 except for the conditions shown in Table 1.
[0105] [Comparative Examples 1 to 4] In Comparative Examples 1 to 4, multi-layer, microporous polyolefin membranes were produced in the same manner as in Example 1 except for the conditions shown in Table 2. In addition, a two-dimensional distribution diagram showing the Raman intensity ratio of PP / PE in Comparative Example 1 is shown in Figure 4. In addition, a two-dimensional distribution diagram showing the Raman intensity ratio of PP / PE in Comparative Example 2 is shown in Figure 5.
[0106] [Comparative Example 5] A multi-layer, microporous polyolefin membrane was produced in the same manner as in Example 4 except for the conditions shown in Table 2.
[0107] Table 1 shows the blend ratio of each component of the produced three-layer microporous polyolefin membrane, the production conditions, and the evaluation results.
[0108]
Table 1
[0109]
Table 2
Claims
1. A multi-layer, microporous polyolefin membrane comprising a first layer containing polypropylene and polyethylene and a second layer made of polyethylene, the multi-layer, microporous polyolefin membrane satisfying the following requirements (I) and (II): (I) The polyolefin multi-layer, microporous membrane has regions in which the Raman intensity ratio of polypropylene to polyethylene is 0.018 or more and 0.040 or less, as determined by micro-Raman spectroscopy, and a network structure in which the regions are interconnected occupies 68% or more of the surface area of the polyolefin multi-layer, microporous membrane, and the coefficient of variation of the Raman intensity ratio of PP / PE is 8% or more and 30% or less. (II) The puncture strength per unit area of the polyolefin multi-layer, microporous membrane (N m 2 / g) divided by the maximum pore size (μm) is 13 or more and 30 or less.
2. The half-width of the Raman band of polypropylene obtained by micro-Raman spectroscopy is 7.20 cm -1 2. The multi-layer, microporous polyolefin membrane of claim 1, wherein:
3. The multi-layer, microporous polyolefin membrane according to claim 1 or 2, having a membrane thickness of 6 μm or less.
4. The multi-layer, microporous polyolefin membrane according to any one of claims 1 to 3, which is used as a battery separator.
5. A laminated multi-layer, microporous membrane comprising a porous layer laminated on at least one surface of the polyolefin multi-layer, microporous membrane according to any one of claims 1 to 3.
6. The laminated, multi-layer, microporous membrane according to claim 5 for use as a battery separator.
7. A method for producing the multi-layer, microporous polyolefin membrane according to any one of claims 1 to 4, comprising the following steps (1) to (6): (1) A step of melt-kneading a first polyolefin resin composition containing polypropylene and polyethylene with a membrane-forming solvent to prepare a first polyolefin solution; (2) melt-kneading a second polyolefin resin composition containing polyethylene with a membrane-forming solvent to prepare a second polyolefin solution; (3) co-extruding and cooling the first and second polyolefin solutions to form a gel-like multilayer sheet; (4) a first stretching step of stretching the gel-like multilayer sheet at 107° C. or more and 112° C. or less; (5) removing the membrane-forming solvent from the stretched gel-like multilayer sheet and drying it; (6) A second stretching step of stretching the dried multilayer sheet in the width direction at 1.55 times or more at 95° C. or more and 130° C. or less.
Citation Information
Patent Citations
Polyolefin-made microporous membrane
JP2010235654A
Microporous polyolefin film
JP2013126765A
Polyolefin microporous film and method for producing same
WO2013099607A1
Multilayer, microporous polyolefin membrane, and production method thereof
WO2014192861A1
Polyolefin multilayer microporous film, method for producing same, and cell separator
WO2015194667A1